Detection of Non-Communicable Disease Risk Using Android-Based Application (Design of DERI PTM Application) - Utama, Feranita; Ningsih, Windi Indah Fajar; Lionita, Widya (Poltekkes Kemenkes Tanjung Karang, 2023)
Non-communicable diseases (NCDs) are chronic diseases often not realized by sufferers and continue to experience a significant increase. They are the largest contributor to the cause of death in the world. NCDs also affect a person's susceptibility to exposure to coronavirus 19 (covid 19) and increase the severity of covid 19 sufferers. This study aimed to design a health application that the community can use for early detection of NCD risk factors, especially modifiable behavioral risk factors and metabolic risk factors. The application design method used the prototype method. Needs analysis and application trials were conducted at Sriwijaya University. A needs analysis was performed by conducting in-depth interviews with five students, three lecturers, three employees, a leadership of faculty, and ahead of the university's healthy campus program. User trial results are evaluated through Zoom and by filling out a questionnaire on Google Forms. The results of the needs analysis survey showed that most users want the design of an Android-based health application that assesses the risk of NCDs and recommendations for the results of risk assessment. In conclusion, an android-based health application has been designed to independently detect the risk of non-communicable diseases under the name DERI PTM. This application can be developed into an effective educational media for preventing and controlling non-communicable diseases in the community. It can be utilized as an information system (surveillance) of NCDs at Sriwijaya University.